Tingkat pengetahuan ibu hamil tentang kurang energy kronis (KEK) di Puskesmas Mergangsan Kota Yogyakarta - Albina Destri Evri Yanti; Suherni Suherni; Ana Kurniati (Jurnal Kesehatan Ibu dan Anak, 2016)
Maternal mortality shows that one of the factors is related to the pregnancy disorders. One of the causes formaternal mortality is chronic lack of energy on pregnancy. Because of having limited knowledge onnutrients,pregnant women are short of nutrients that are actually useful for their pregnancy. Basically,knowledge on nutrition is extremely useful for pregnant women. The prevalence ofCLE in the city of Yogyakartais 19.42%. Meanwhile, the prevalence of OLE at the Public Health Center of Mergangsan is 36.49%. Thisresearch is conducted to find out the knowledge level of pregnant women on CLE at the Public Health Center ofMergangsan, city of Yogyakarta. It is a descriptive research with the survey design of cross-sectional approach.The subject is all pregnant women who pay a visit for their pregnancy check-up to the Public Health Center ofMergangsan on May 28th and June 3rd and 4th, 2014. In accordance with the criteria, 40 respondents are takenforthis research. Univariateanalysis is amethod used to analyze the data. Most of the respondents are between20 and 35 years old (77.50%), high school leavers (57.50%), not working (75%), and primipara parity (67.50%).The knowledge level on CLE is sufficient if based on their age (70.83%), if based on their majority educationbackground (50%), if based on their working status (83.33%), and if based on primipara parity (62.50%). Inshort, the knowledge level of pregnant women on CLE at the Public Health Center of Mergangsan, city ofYogyakarta, is sufficiently categorized (60%).